PROSES PERENCANAAN TOTAL QUALITY MANAGEMENT DALAM PENDIDIKAN ISLAM - FITRIANI, FITRIANI (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This paper describes the Total Quality Management (TQM) planning process in Islamic education. Planning is needed in every process of activity. Without a clear long-term direction, an agency can not plan for quality improvement. Total Quality Management process in Islamic education is more or less the same as the Total Quality Management process in general, its by looking at input that is what is needed, desired, or expected from learners. Then, the process of learning can be seen how the level of quality of an educational institution that is how the quality of output.